K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

19 tháng 10 2020

\(\left(x+3\right)\left(x^2-3x+5\right)=x^2+3x\)

\(\Leftrightarrow\left(x+3\right)\left(x^2-3x+5\right)=x\left(x+3\right)\)

\(\Leftrightarrow\left(x+3\right)\left(x^2-3x+5\right)-x\left(x+3\right)=0\)

\(\Leftrightarrow\left(x+3\right)\left(x^2-3x+5-x\right)=0\)

\(\Leftrightarrow\left(x+3\right)\left(x^2-4x+5\right)=0\)

\(\Leftrightarrow\orbr{\begin{cases}x+3=0\\x^2-4x+5=0\end{cases}}\Leftrightarrow x=-3\)< vì x2 - 4x + 5 = ( x2 - 4x + 4 ) + 1 = ( x - 2 )2 + 1 ≥ 1 > 0 ∀ x

19 tháng 10 2020

\(\left(x+3\right)\left(x^2-3x+5\right)=x^2+3x\)

\(\Leftrightarrow x^3-3x^2+5x+3x^2-9x+15=x^2+3x\)

\(\Leftrightarrow x^3-4x+15=x^2+3x\)

\(\Leftrightarrow x^3-x^2-7x+15=0\)

\(\Leftrightarrow\left(x^2-4x+5\right)\left(x+3\right)=0\Leftrightarrow x=-3\)

15 tháng 8 2020

a, 15x3 - 15x = 0    

15x(x2-1)=0

15x=0 hoặc x2-1=0  (tự tính nhoa)

b,3x2-6x+3=0

3(x2-2x+1)=0

x-2x+1=0:3=3

x2-2x=3-1=2

x(x-2)=0

x=0 hoặc x-2=0 (tự tính nhoa)

15 tháng 8 2020

Bài làm

a) 15x3-15x=0

<=> 15x( x2 - 1 ) = 0

<=> \(\orbr{\begin{cases}15x=0\\x^2-1=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x=0\\x=\pm1\end{cases}}}\)

Vậy x = { 0; + 1 }

b) 3x- 6x + 3 = 0

<=> 3( x2 - 2x + 1 ) = 0

<=> x2 - 2x + 1 = 0

<=> ( x - 1 )2 = 0

<=> x - 1 = 0

<=> x = 1

Vậy x = 1

c) 5(x - 1) - 3x(1 - x) = 0

<=> 5(x - 1) + 3x(x - 1) = 0

<=> (5 + 3x)(x - 1) = 0

<=> \(\orbr{\begin{cases}5+3x=0\\x-1=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x=-\frac{5}{3}\\x=1\end{cases}}}\)

Vậy x = { -5/3; 1 }

e) -7(x + 2) = 2x(x + 2) 

<=> -7(x + 2 ) - 2x( x + 2 ) = 0

<=> (x + 2)(-7 - 2x) = 0

<=> \(\orbr{\begin{cases}x+2=0\\-7-2x=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x=-2\\x=-\frac{7}{2}\end{cases}}}\)

Vậy x = { -2; x = -7/2 }

f)(2x - 3)(3x + 5) = (x - 1)(3x + 5)

<=> (2x - 3)(3x + 5) - (x - 1)(3x + 5) = 0

<=> (3x + 5)(2x - 3 - x + 1) = 0

<=> (3x + 5)(x - 2) = 0

<=> \(\orbr{\begin{cases}3x+5=0\\x-2=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x=-\frac{5}{3}\\x=2\end{cases}}}\)

Vậy x = { -5/3; 2 }

26 tháng 6 2016

\(a.x\left(x-5\right)\left(x+5\right)-\left(x+2\right)\left(x^2-2x+4\right)=3\)

\(\Leftrightarrow x\left(x^2-5^2\right)-\left(x^3+2^3\right)=3\)

\(\Leftrightarrow x^3-25x-x^3-8=3\)

\(\Leftrightarrow x^3-x^3-25x=8+3\)

\(\Leftrightarrow x=\frac{11}{-25}\)

Vậy x có nghiệm là \(\frac{-11}{25}.\)

\(\)

3 tháng 10 2016

de qua

6 tháng 8 2018

x.(2.x-1)+1/3-2/3.x=0

18 tháng 6 2016

f/ \(3xy\left(x+y\right)-\left(x+y\right)\left(x^2+y^2+2xy\right)+y^3=27\)

\(3x^2y+3xy^2-\left(x+y\right)\left(x+y\right)^2+y^3=27\)

\(3x^2y+3xy^3-\left(x+y\right)^3+y^3=27\)

\(3x^2y+3xy^3-\left(x^3+3x^2y+3xy^2+b^3\right)+y^3=27\)

\(-x^3=27\)

\(x=-3\)

18 tháng 6 2016

Bài 1:

a/ \(3\left(2x-3\right)+2\left(2-x\right)=-3\)

\(6x-9+4-2x=-3\)

\(4x=-2\)

\(x=-\frac{1}{2}\)

b/ \(2x\left(x^2-2\right)+x^2\left(1-2x\right)-x^2=-12\)

\(2x^3-4x+x^2-2x^3-x^2=-12\)

\(-4x=-12\)

\(x=\frac{1}{3}\)